Confronting Rapid Reemergence of COVID-19 in Metropolitans of Vietnam: Updated Vietnam's Policies and Response Measures - Le, Anh Minh; Dao, Nam Gia; Latkin, Carl A.; Vu, Linh Gia; Dam, Vu Anh Trong; Vu, Giang Thu; Ho, Cyrus S. H.; Ho, Roger C. M. (Frontiers in Public Health, 2022)
Vietnam has demonstrated the effectiveness of precise prevention and control techniques from the very beginning during the three COVID-19 outbreaks. However, the fourth COVID-19 wave, which began in mid-2021, has been considered significantly more dangerous. These challenges required the Vietnamese government to make timely adjustments to the current COVID-19 prevention effort in time to prevent disease spread in the community. According to the Ministry of Health, the COVID-19 epidemic prevention and control strategy has three significant changes: increasing capacity for testing and vaccination, boosting interdisciplinary collaboration, and adjusting quarantine, treatment, and social support policies.